Design and Build A Portable Smart Trash With Metal & Non Metal Separator - St. Nurhayati Jabir; Wahidah; Sari Wahyuni (Engineering and Technology International Journal, 2022)
Garbage is one of the causes of environmental pollution. In waste disposal, people usually combine metal and non-metal waste in one place so that the quality of environmental health decreases. This study aims to create a portable smart trash can with Metal & Non Metal separator. This research is an experimental research conducted through two stages, namely the design stage and the testing stage. This system consists of metal detector, ultrasonic sensor, IR proximity sensor, Inductive Proximity Sensor and servo motor. The test results are that the lid will automatically open because it is driven by a servo motor if the ultrasonic sensor detects the presence of a maximum human within 72 cm. If the metal and non-metal trash bins are full the lid will not open and the buzzer will sound. Furthermore, when inserting trash, if the inductive proximity sensor and capacitive proximity sensor is worth 1 then what is detected is metal trash and the servo will rotate and direct the trash to the metal bin. Likewise, if only the capacitive proximity sensor has a value of 1 and the inductive proximity sensor detects a metal value of 0, the servo will rotate and direct the garbage to the non-metal trash can.